Heat-induced changes in the sensory properties of milk. (March 2022) - Coolbear, Tim; Janin, Nathalie; Traill, Rachel; Shingleton, Rebecca
Abstract: Heat treatment of milk to extend its shelf life by reducing the potential of microorganisms and enzymes to make the product unsafe or spoil has consequences on its organoleptic qualities. The greater the heat load, the greater are the consequences; the different combinations of time and temperature applied in the creation of the range of liquid milk products manufactured by the dairy industry present a range of compromises between extending shelf-life and minimising changes in the original sensory characteristics that are adverse to consumer acceptance. This review looks at the sensory changes that are brought about by the heat treatments applied across thermisation, pasteurisation, ultra-high temperature treatment, in-container sterilisation and, since it represents much of the global consumption, milk powders for recombining. Consideration of heat treatment is also extended to heat loading encountered in the supply chain and to reduction of overall heat loads through application of alternative, non-thermal technologies.